Client 9 [videorecording (DVD)] : the rise and fall of Eliot Spitzer - Gibney, Alex; Gibney, Alex (Magnolia Home Entertainment, 2011)
When he was NY's Attorney General, Eliot Spitzer prosecuted crimes by America's largest financial institutions and some of the most powerful executives in the country. After his election as governor, with the largest margin in the state's history, many believed Spitzer was on his way to becoming the nation's first Jewish president. Then, shockingly, Spitzer's meteoric rise turned into a precipitous fall when the New York Times revealed that Spitzer had been caught seeing prostitutes.